2011
DOI: 10.1152/ajpheart.00222.2011
|View full text |Cite
|
Sign up to set email alerts
|

Prostaglandins do not contribute to the nitric oxide-mediated compensatory vasodilation in hypoperfused exercising muscle

Abstract: Casey DP, Joyner MJ. Prostaglandins do not contribute to the nitric oxide-mediated compensatory vasodilation in hypoperfused exercising muscle. Am J Physiol Heart Circ Physiol 301: H261-H268, 2011. First published May 2, 2011; doi:10.1152/ajpheart.00222.2011.-We tested the hypothesis that 1) prostaglandins (PGs) contribute to compensatory vasodilation in contracting human forearm subjected to acute hypoperfusion, and 2) the combined inhibition of PGs and nitric oxide would attenuate the compensatory vasodilati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
1

Year Published

2012
2012
2019
2019

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 34 publications
0
12
1
Order By: Relevance
“…In general, changes in arterial oxygen content evoke either increases (hypoxia) or decreases (hyperoxia) in blood flow with the net effect of maintaining constant oxygen delivery to the contracting muscles (73, 80 -83, 182, 399, 504, 509, 510). A similar compensatory vasodilator response is seen when oxygen delivery is reduced by lowering perfusion pressure via balloon inflation to the contracting muscles (74,75,(77)(78)(79).…”
Section: O Blood-borne Vasodilator Substancesmentioning
confidence: 80%
See 1 more Smart Citation
“…In general, changes in arterial oxygen content evoke either increases (hypoxia) or decreases (hyperoxia) in blood flow with the net effect of maintaining constant oxygen delivery to the contracting muscles (73, 80 -83, 182, 399, 504, 509, 510). A similar compensatory vasodilator response is seen when oxygen delivery is reduced by lowering perfusion pressure via balloon inflation to the contracting muscles (74,75,(77)(78)(79).…”
Section: O Blood-borne Vasodilator Substancesmentioning
confidence: 80%
“…However, a combination of downstream vasodilation and collateral circulation around the elbow permitted the blood flow responses to submaximal forearm exercise to recover rapidly (FIGURE 12). At steady state, they were remarkably normal (74,75,78,79,85).…”
Section: A Site Of the Vasodilationmentioning
confidence: 97%
“…In the same light, it was noted by Schrage et al (2004) that both NO and PGs contribute to exercise hyperemic responses independently, with some emphasis on a larger role for NO as compared to PGs. In a model using partial intra-arterial ischemia during exercise, NO synthase inhibition was noted to blunt vasodilatory responses, however this response was noted to be independent of PGs Casey and Joyner 2011). Naylor et al (1999) compared ischemia alone and ischemic exercise hyperemic responses with and without systemic prostaglandin blockade using indomethacin and ibuprofen.…”
Section: Discussionmentioning
confidence: 99%
“…A review of the repeatability data for this ischemic exercise model showed a trend of increasing baseline blood flow for each successive trial that may have masked effects of drug infusion on baseline flow (Lopez et al 2012). This was despite evidence from Doppler ultrasound studies using beat-to-beat blood velocity measures that a 20-min resting period was adequate for blood flow to return to baseline following handgrip exercise (Casey and Joyner 2011). The use of VOP and thus postexperiment data analysis precluded the ability to ensure a complete return to baseline after resting periods.…”
Section: Experimental Considerationsmentioning
confidence: 99%
“…Hypoperfusion models (Casey & Joyner, 2009b, 2011b have demonstrated that compensatory vasodilatation during moderate intensity exercise is mediated in part by NO (ß20%; Casey & Joyner, 2009a) and adenosine (ß19%; Casey & Joyner, 2011a), whereas prostaglandins are not obligatory (Casey & Joyner, 2011c). The red blood cell acting as an oxygen sensor would appear to be a prime candidate for compensatory vasodilatation given the impairment to flow at a fixed metabolic demand (Dietrich et al 2000;Ellsworth, 2000;González-Alonso, 2012).…”
Section: Mechanisms Of Compensatory Vasodilatationmentioning
confidence: 99%